Effect of Allopurinol in Chronic Kidney Disease Progression in Asymptomatic Hyperuricaemic Subjects - Anwar, ASM Tanim; Chowdhury, Md Nizamuddin; Islam, Md Nazrul; Ahmed, Parvez Iftekher; Sweety, Sohely Ahmed; Hasan, Rafiqul (Journal of Dhaka Medical College, 2017)
This was a hospital based prospective, interventional study which included CKD stage 3- 5 patients with higher level of uric acid (male>7mg/dl, female>6mg/dl). The objective of the study was to evaluate the effect of allopurinol in chronic kidney disease (stage 3-5) progression in asymptomatic hyperuricaemic patients.One hundred and twenty patients were distributed in two groups. Sixty patients were placed in treatment group and sixty in control group. Purposive sampling technique was followed. In the study mean age was 49 (±9) years in treatment group and 45 (±11) years in control groups. Male were predominant in both groups. There were no significant difference in baseline characteristics between treatment group and control group (p>0.05). Sixty patients of treatment group were administered a dose of 100 mg/d of allopurinol. Follow up assessment was done at basally, at 4 months and at 8 month after starting treatment. No significant differences were seen between baseline SBP, DBP, Hb and HbA1c with 4th month and 8th month follow up in both treatment group and control group, but mean Hb was significantly decreased in control group from the baseline after 8 month. Serum uric acid was decreased in treatment group while it was significantly raised from the base line at 4th month and 8th month in control group. In treatment group serum creatinine was decreased and eGFR was raised from the baseline after 8 month. On the other hand, in control group serum creatinine was significantly raised and eGFR was significantly decreased from the baseline at 8th month. While comparing between two groups results showed means of serum uric acid was significantly decreased in treatment group compared to control group after 8th month. There was a negative correlation between Uric Acid with eGFR after 8 month of allopurinol treatment although this finding was not statistically significant. So, allopurinol may have a protective role in CKD progression by decreasing serum uric acid level in patients with chronic kidney disease stage 3 - 5 with asymptomatic hyperuricaemia. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 5-15